The criteria for the ergodicity of the homogeneous Markov chains with special phase space. I - Navickas, Z. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:З. Навицкас. Критерии эргодичности однородных марковских цепей в специальном фазовом пространстве. IZ. Navickas. Homogeninių Markovo grandinių, definuotų specialioje fazinėje erdvėje, ergodiškumo kriterijai. I